The Merit and Beyond; Portraying Student Exchange as Synergetic International Relations - Anggraini, Risa (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2024)
The breakthrough on developing the synergy of international relations among countries is by fostering student exchange as the so-called worthwile programs that link the bilateral relationship and cultural identities. These student exchange programs accentuate the mutual liaison among the countries. It, indeed, exerts influence on students both positively and unforgettably. This research was designed in qualitative method and researcher utilized inquiry strategy of phenomenological study. Three main informants were participated in this research because they experienced the student exchange in advance. Researcher gathered the data through in-depth interview. Specifically, there were four major themes found in the research, they were 1) The lifetime experiences, 2) The challenges and barriers, 3) The problem solving, and 4) The impacts and changes. These findings highlighted the primary goal of the student exchange program itself and also fostered interconnection among the countries in forging impacts for the students as well as the country they belong to. Keywords: Student Exchange, Synergetic Impacts, and International Relations.